Aspects of the bionomics of Brackish Water Prawn (Macrobrachium macrobrachion: Herklots 1851) in the interconnecting lagoons of South-Western Nigeria. Issue 1 (1st January 2021) - Akinwunmi, M. F; Moruf, R.O
ABSTRACT: Macrobrachium macrobrachion is a caridean shrimp native to brackish and fresh waters of West Africa and is also considered to have potential for aquaculture and other research purposes. The bionomics of M. macrobrachion from Badagry, Lagos and Epe Lagoons were investigated monthly for 24 months between June 2013 and May 2015. The sex ratio revealed that there were more females from Badagry and Lagos Lagoons with males dominating Epe Lagoon. The fecundity estimates from the three lagoons ranged between 760 and 84, 850 eggs with a weak correlation (R < 0.5). The mean GSI values ranged between 1.76 and 35.29% and showed that there were no significant differences (P > 0.05) in M. macrobrachion from Badagry and Lagos Lagoons while the GSI values from Epe Lagoon was significantly different (P < 0.05) from other lagoons. The egg diameter from the three lagoons ranged from 258 to 450 μm with no significant differences (P > 0.05) in the values. The dominance of females in Badagry and Lagos Lagoons could be attributed to the fact that both lagoons are salty and the females require such conditions to spawn while males dominated Epe Lagoon. The scientific observations documented in this study, will therefore serve as important references in the species assessment, cultivation, management and conservation of the prawn fisheries.